KAJIAN BIBLIKA TERHADAP MAKNA “” BERDASARKAN MATIUS 5:17-20 - Rantung, Wilson (Ambassadors: Jurnal Teologi dan Pendidikan Kristiani, 2022)
Obedience to the Law was seen as an important part of religious life in Jewish society. Thus everyone cannot be separated from the demand for obedience to the Law, because Obedience to the Law in Judaism is very closely related to the concept of Justification (dikaios). Therefore, belief is justified based on obedience to the Law, has been entrenched in the life of the Jewish community in general, thus influencing the attitudes and behavior of the Jews towards God and His Torah from generations. The presence and teachings of the Lord Jesus received great rejection from Judaism, the presence and teachings of Jesus were considered as distorting the truth or misleading. The investigation in this paper will include Biblical Studies, namely obtaining a proper, adequate and solid understanding of a text by taking into account the position of the interpreter as a third party, so as to produce the actual truth to fulfill the purpose of the writing